Az állattartás területi sajátosságai Magyarországon - Széles, Gyula (Tér és Társadalom, 1996)
In the years of 1990-1995 both the volume and the share of the foreign currency incomes declined as a consequence of the significant decrease in the number of the livestock. The unfavourable developments in the export mainly struck the meat processing industry, which could be seen in the decline of the export of both pigs and cattle and of pork and beef. This brought about several economic consequences, from which the following should be emphasised: Meat processing industry is one of the leading sectors of the Hungarian agricultural economy, thus its development takes a significant sacrifice from the national economy, on the other hand, the decreasing number of livestock brings about problems of the capacity utilisation, which, because of the increase in fixed 'costs, further worsens the international competitiveness of the Hungarian agricultural products. The essay analyses in details the regional features of the changes in the number cattle, within this cows, also the total number of pigs, with special regard to sows, in the period 1991-1995. It emphasises that the decrease in the number of cattle and cows shows differences among the regions and it concems regions where the ecological and economic conditions for keeping cattle are much more favourable than the national average. The analyses covers the breakdown of the cattle and cow stock by economic organisations, where the author uses the following categories: Firms and economic companies, co-operatives and private smallholders. The data show significant regional differences here, as well. The study provides a detailed analysis of the regional features of the development of the number of pigs and sows in the years of 1991-1995. It emphasises that in this respect there are smaller differences compared to the national average. It also points to the fact that in the number of pig-stock, in some regions the integrating activities of the meat processing companies can be palpable. The essay underlines that the volume of the decrease in the number of livestock that took place in Hungary is unique in the world economy and even in Eastern and Central Europe. Finally, the author analyses in details the factors which in his opinion are dominant for the large decline of the livestock. Within the economic factors, he gives a special emphasis to the strong pressure caused by financial and liquidation issues.